1974
DOI: 10.1289/ehp.7477
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Hematologic Responses to Increased Lead Absorption in Young Children

Abstract: In the study of human populations, much emphasis is placed on the concentration of lead in whole peripheral blood. There is a considerable body of evidence which indicates that this measurement reflects recent and current assimilation of lead. While broad ranges in blood lead concentration have been associated with differing risks of toxicity for groups, it is not a precise index of adverse effect per se, even at elevated levels. Within the red blood cell itself there is not a close association between the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The differ¬ ence between the two means is highly significant (i = 4.38, < .001). The 24-hour collections before and during edetate disodium calcium provocation show a remarkable outpouring of lead in four cases: subjects 7 (700 µg/liter), 20 (683 /xg/liter), 21 (1,036^g/liter), and 22 (695 fig/liter). Although the size of the sample is small, it can be observed that of the seven children initially selected, on the basis of slowed MNCV at a level of at least 1 SD, as being suspect of increased body lead burden, a possible relationship exists between the MNCV slowing and the quantity of lead excreted in the urine after edetate disodium calcium provocation.…”
Section: Comment On Casesmentioning
confidence: 95%
“…The differ¬ ence between the two means is highly significant (i = 4.38, < .001). The 24-hour collections before and during edetate disodium calcium provocation show a remarkable outpouring of lead in four cases: subjects 7 (700 µg/liter), 20 (683 /xg/liter), 21 (1,036^g/liter), and 22 (695 fig/liter). Although the size of the sample is small, it can be observed that of the seven children initially selected, on the basis of slowed MNCV at a level of at least 1 SD, as being suspect of increased body lead burden, a possible relationship exists between the MNCV slowing and the quantity of lead excreted in the urine after edetate disodium calcium provocation.…”
Section: Comment On Casesmentioning
confidence: 95%
“…Exposure during childhood is thought to be brief, usually until the age of 6 [ 31 ]; however, the side effects persist throughout life [ 32 ]. Possible sources for lead include: leaded paint, lead contaminated soil, lead in plumbing, automobile exhaust, by-products of both mining and metal working, and various consumer products [ 18 , 33 , 34 , 35 , 36 ]. After the ill effects of lead on people’s health were recognized, lead was first banned in Europe in the early 1900s [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experts seem to agree: "Too much reliance must not be placed on the figures for blood lead" says Hunter2; "It is not a precise index of adverse effect per se, even at elevated levels" warns Chisolm3; "Its main value is to monitor abnormal exposure in a population rather than to serve as a major diagnostic tool" concludes Waldron.4 These opinions, however cautiously expressed, clearly suggest the diagnostic irrelevance of the blood lead concentration in clinical poisoning, the more so because the concentrations "return to normal even though exposure was excessive". 3 Nevertheless, a "diagnostic" lead blood concentration has been taken as the basis for a nationwide plan to eradicate childhood lead poisoning in the United States and a "call for lowering of the definition (sic) of lead poisoning from a blood lead level of 25ug/dl (1-20 mmol/l) to 10,ug d/l (0-050 mmol/l)".5 This still seems to be of concern as some authors6 have established a blood concentration of 0-016 ,ug/dl as the "natural" blood lead concentration and announced that there may be no threshold concentration for lead toxicity. "Preventive medicine's latest goal"5 could be of course idealistically and enthusiastically ex officio proclaimed to be a zero lead blood concentration but only if we take all the lead out of air and the diet or only after we change the geochemistry of our planet.…”
mentioning
confidence: 99%